Effects of Nutrition Education on Anthropometric Indices, Biochemical and Sonographic Findings of Patients with Non-alcoholic Fatty Liver Disease (NAFLD) - Masoumeh Tehrani; Zahra Baji; Ghodratollah Shakerinejad; Saeedeh Hajinajaf; Farzaneh Jarvandi; Maryam Saki (Iranian Association of Health Education and Health Promotion, 2017)
Background and objective: Nonalcoholic fatty liver disease (NAFLD) is one of the most common liver disease. It occurs most commonly among obese and overweight people. This study was performed to determine the effect of nutrition education on anthropometric indices, biochemical and sonographic findings in patients with NAFLD Referring to Khuzestan Diet Therapy clinic, Academic Center for Education, Culture and Research (ACECR), Branch of Khuzestan, in Ahvaz, Iran. Materials and methods: This study was a before and after interventional study carried out on 30 NAFLD patients. Selected variables were evaluated at the time before and after three month intervention by nutrition education for patients. SPSS 19 and statistical tests, including descriptive, paired samples t-test and non-parametric sign test was used to analysis the data. Results: The average age of the patients were 44.8 ± 11.2 years. Anthropometric indices decreased significantly after three months nutrition education intervention (p< 0.001). Hepatic enzymes and lipid profiles declined at the end of intervention in which it was only statistically significant about ALT and AST (p< 0.001). Sonographic findings of patients indicated a significant reduction in severity and grade of disease after intervention. Conclusion: Nutrition education could affect the anthropometric and biochemical indices and improve the liver function of NAFLD patients. Paper type: Research Article.